"U", in or out? : Americanisms in George Washington's Lexicon in the 18th Century - Summanen, Elsa (My University, 2024)
This thesis focuses on the use of American versus British spellings of the words honour/honor and favour/favor in 18th century United States through the language used by George Washington in his personal correspondence. The data being analyzed in the study consist of 400 individual letters written by Washington between the years 1752 and 1767, and 1783 and 1796. The data was analyzed by counting the number of times these words appeared in the chosen documents to determine whether one spelling variation was featured more prominently than the other and whether there was a noticeable difference between the earlier and the later documents and what the motivations behind any possible changes could be. The results showed that the American variations of these words were used considerably more across all samples and continued to rise in prominence towards the end of the 18th century. Meanwhile, the use of the British variations decreased within the same time frame. This can be directly linked to the efforts to reform the English language in America during and after the American Revolution. Based on the results and the context with which they are viewed, it can be assumed that Washington could have made the deliberate choice to prefer the American spelling of these words in his writing to show his support for the efforts to establish a distinct American orthography, as well as identity, following independence from Britain.
Keywords: American English, linguistic change, spelling, Americanization, lexicography, American history, dictionaries